2017
DOI: 10.1103/physrevphyseducres.13.010129
|View full text |Cite
|
Sign up to set email alerts
|

Value added or misattributed? A multi-institution study on the educational benefit of labs for reinforcing physics content

Abstract: Instructional labs are widely seen as a unique, albeit expensive, way to teach scientific content. We measured the effectiveness of introductory lab courses at achieving this educational goal across nine different lab courses at three very different institutions. These institutions and courses encompassed a broad range of student populations and instructional styles. The nine courses studied had two key things in common: the labs aimed to reinforce the content presented in lectures, and the labs were optional.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 39 publications
(83 reference statements)
3
58
0
2
Order By: Relevance
“…One implicit measure of the extent to which these courses are valued by the physics community is that the majority of undergraduate physics programs in the United States include at least two required lab courses. However, historically, little work has been done clearly demonstrating the effectiveness of these courses at achieving their learning goals [1][2][3]. Recently, demonstrating student learning in undergraduate lab courses has been the focus of additional attention from the physics education research community [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…One implicit measure of the extent to which these courses are valued by the physics community is that the majority of undergraduate physics programs in the United States include at least two required lab courses. However, historically, little work has been done clearly demonstrating the effectiveness of these courses at achieving their learning goals [1][2][3]. Recently, demonstrating student learning in undergraduate lab courses has been the focus of additional attention from the physics education research community [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to specific research on light and spectroscopy, there is a growing body of research on demonstrations and labs showing that these are often ineffective in promoting student learning of the intended physical concepts-and may even be counterproductive [10][11][12][13]. Crouch et al [14], for example, found no significant difference between students who had and had not observed certain demonstrations.…”
Section: Prior Researchmentioning
confidence: 99%
“…Even laboratory experiments that, on the surface, appear designed to engage students in their learning may not have an impact on student conceptions. Wiemann and Holmes [10] and Holmes et al [11] analyzed the effect of taking a lab course on student learning in introductory calculusbased physics courses. The labs were well coordinated with the lectures and included prelab activities that consisted of sequences of questions that led students to make predictions and explore the relevant physics concepts.…”
Section: Prior Researchmentioning
confidence: 99%
“…Likely, at least in part, for this reason, and similar to electronics, optics lab courses are often seen in upper-division physics programs, as well as in optics programs, and optical engineering programs. However, there is recent evidence from physics education research (PER) that students struggle to learn theoretical physics concepts from laboratory exercises 1,2 . This literature suggests, however that laboratory courses may still be quite useful for teaching knowledge and skills particularly relevant to experiments 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is recent evidence from physics education research (PER) that students struggle to learn theoretical physics concepts from laboratory exercises 1,2 . This literature suggests, however that laboratory courses may still be quite useful for teaching knowledge and skills particularly relevant to experiments 1,2 . Conversely, the idea that students would learn experimental/applied skills from studying theoretical physics is very counter-intuitive.…”
Section: Introductionmentioning
confidence: 99%